1987
DOI: 10.1016/0014-5793(87)80667-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid antagonists

Abstract: The three principal areas of application of hormone antagonists are: clinical, diagnostic, and delineation of hormone action ([l-5] for reviews). Inhibition of synthesis of glucocorticoids in the adrenal cortex was attempted nearly three decades ago using metyrapone and aminogluthemide derivatives [3,5], and more recently with antimycotic agents [6,7]. Some 45 years ago androgens and superandrogens R 2999 and R 4841 [8-l 11, progesterone [12,13] It is generally admitted that adrenocorticoid hormone action proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Both Dex and RU38486 bind to the membrane‐bound glucocorticoid receptor (Chen et al ., 1993; Quelle et al ., 1988) but the binding‐affinity of RU38486 is greater than that of Dex (Chen et al ., 1993). RU38486 also has a high affinity for the cytosolic glucocorticoid receptor and is a reliable competitive antagonist of this receptor (Agarwal et al ., 1987). This compound has no agonist activity at either receptor.…”
Section: Methodsmentioning
confidence: 99%
“…Both Dex and RU38486 bind to the membrane‐bound glucocorticoid receptor (Chen et al ., 1993; Quelle et al ., 1988) but the binding‐affinity of RU38486 is greater than that of Dex (Chen et al ., 1993). RU38486 also has a high affinity for the cytosolic glucocorticoid receptor and is a reliable competitive antagonist of this receptor (Agarwal et al ., 1987). This compound has no agonist activity at either receptor.…”
Section: Methodsmentioning
confidence: 99%
“…However, the regulatory mechanisms of fatty acid biosynthesis are still poorly understoocL We have demonstrated that the regulatory action of gluc~ corticoid hormones on the fatty acid desaturase activities depends on a protein factor whose biosynthesis is brought about by hormonal induction (1,3). Although ll<leoxycorticosterone (DOC) does not have an 11-/Y-hydroxy group, which is thought to be essential for glucocorticoid activity (6), we have previously demonstrated that in HTC cells this hormone can induce a soluble regulatory factor that stimu-lares A9 desaturase activity (7). Two species of adrenoco~ tical hormone receptors have been definecE i) Those receptom associated with mineralocorticoid function which have a high affinity for aldosterone (ALDO) and a lower affinity for corticosterone (8); and ii) those receptors associated with glucocorticoid function which have a high affinity for cot ~ ticosterone and a lower affinity for aldosterone (9,10).…”
Section: Lipids 27 599-604 (1992)mentioning
confidence: 99%
“…RU 38486 has a high affinity to glucocorticoid's cytosolic receptor but has no agonist effect, so it is a competitive antago nist of glucocorticoid receptor [ 1 ]. RU 38486 alone exerted no influences on either membrane potential or input resistance of the cell.…”
Section: Intracellular Microelectrode Study On Isolated Coeliac Ganglmentioning
confidence: 99%